Educação de jovens e adultos : direito, concepções e sentidos - Paiva, Jane (2005)
At present, programs and projects in the area of Youth and Adult Education have been unveiling different ways of understanding and apprehending the meanings and needs which emerge in the various groups who are in search of such educational proposals, less so with life-long education in perspective than to assert their right to education, a right that has systematically been denied to so many Brazilians. Based on this initial premise, this study has explored the different ways in which six organizations have formally stated their postulates as well as carried out their practical work in this area. Such organizations are characterized by being public, non-governmental, and pertaining to the Social Movement and the S System. The aim of the study is to comprehend such postulates and practices, in the light of the national and international youth and adult educational policies, as well as the interconnections, meanings, nexus, articulations and overlappings which are produced within and beyond their dominions, more precisely inside the complex social network. Impelled by a view centered on rights, this investigation has attempted to gain access to the different layers of reality, so as to make it possible for the productions underlying those programs and projects to emerge, for the sake of mapping out the complexity of that practice, thus identifying and giving visibility to the elements which are constitutive and institutive of their conceptions.